ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN LABA PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING - Sholehah, Dhaimatus; Wiryaningtyas, Dwi Perwitasari; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This study aims to analyze factors that influence profitability in mining companies listed on Indonesian Stock Exchange (IDX) with dividend policy as an intervening variable. The population of this study is all coal mining companies listed on Indonesian Stock Exchange (IDX) involving 28 companies. The sampling technique uses purposive sampling by choosing 10 samples. Data analysis and hypothesis testing use Partial Least Square - Structural Equation Modeling (PLS-SEM). Hypothesis testing of direct and indirect effect use Smart PLS 3.0 application. The results of direct effect hypothesis testing indicate that liquidity has a positive but not significant effect on dividend policy, liquidity and solvency have a negative but not significant effect on profitability, and dividend policy has a significant negative effect on profitability. The results of indirect effect testing show that liquidity has a positive but not significant effect on profitability through dividend policy, solvency has a negative but not significant effect on profitability through dividend policy.